RC beam models damaged and strengthened with GFRP strips under bending loading and free vibration. (1st December 2020) - Capozucca, R.; Magagnini, E.
Abstract: Four reinforced concrete (RC) beam models undamaged, damaged by notches and strengthened by external bonded (EB) glass fiber reinforced polymer (GFRP) strips have been experimentally studied. The paper aims to assess the availability of strengthening with EB GFRP strips in RC beams having a deep localized damage. The behavior of RC beams has been analysed under bending loading until failure. Furthermore, the assessment of RC beam models foresaw nondestructive control of damaged and strengthened models by free vibration tests to obtain frequency values at different damage degree. Damage, artificially obtained by notches with different width, on the midspan section and on the lateral location of beams, has been analysed. The envelope of frequency response functions (FRFs) obtained by dynamic tests was elaborated and changes of natural frequency values are then correlated to damage both to non-strengthened beam with notches and to strengthened beam models. Results of static tests on RC beams strengthened with filled mortar in the notched sections and EB GFRP strips have allowed to validate the strengthening of RC elements with composite material characterized by relatively low elastic modulus; further, it has been assessed maintenance of bond between concrete surface and GFRP strips until failure under bending loading.